The 1st International Electronic Conference on Biomolecules: Natural and Bio-Inspired Therapeutics for Human Diseases 2020
DOI: 10.3390/iecbm2020-08805
|View full text |Cite
|
Sign up to set email alerts
|

In-Vitro Antidiabetic Propensities, Phytochemical Analysis, and Mechanism of Action of Commercial Antidiabetic Polyherbal Formulation “Mehon”

Abstract: Present investigation assessed the hypoglycemic potential of hydro-alcoholic (HAE) and aqueous (AQE) extracts of Mehon, a commercial antidiabetic polyherbal formulation using various in vitro techniques. HAE and AQE were analyzed for α-amylase and α-glucosidase inhibition, glucose adsorption, diffusion, and transport across yeast cells membrane. HAE showed higher αglucosidase (IC50:156.95 μg/ml) inhibition. Glucose adsorption increased with increment in glucose concentration (5mM/L-100mM/L). Rate of glucose up… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 19 publications
0
14
0
Order By: Relevance
“…This activity is thought to be due to the formation of osidic bonds following the complexation of glucose by the hydroxyl groups of flavonoids to form glycosyl flavonoids. 48 Sapadipa et al 49 have also shown the ability of a polyherbal formulation called Mehon to adsorb glucose. All 3 formulations also stimulated peripheral glucose uptake by both yeast cells ( Figure 2 ) and muscle cells ( Table 5 ).…”
Section: Discussionmentioning
confidence: 99%
“…This activity is thought to be due to the formation of osidic bonds following the complexation of glucose by the hydroxyl groups of flavonoids to form glycosyl flavonoids. 48 Sapadipa et al 49 have also shown the ability of a polyherbal formulation called Mehon to adsorb glucose. All 3 formulations also stimulated peripheral glucose uptake by both yeast cells ( Figure 2 ) and muscle cells ( Table 5 ).…”
Section: Discussionmentioning
confidence: 99%
“…The global prevalence of diabetes has reached epidemic proportions, and with worldwide incidence projected to increase from 424 million in 2017 to 629 million by 2045 (IDF, 2017) the global economic burden of the disease can be expected to reach a crescendo. The management of DM through oral hypoglycemic agents and insulin as well as the combination of both which are currently being used is bedeviled with toxic side effect and ineffectiveness (Paul and Majumdar, 2021). In view of these associated side effects and limitations of current drugs, continuous research on natural sources which are believed to be safer, is being conducted to develop new formulations for effective management of DM and the related complications (Chattopadhyay, 1999).…”
Section: Research Paper Open Accessmentioning
confidence: 99%
“…In view of these associated side effects and limitations of current drugs, continuous research on natural sources which are believed to be safer, is being conducted to develop new formulations for effective management of DM and the related complications (Chattopadhyay, 1999). Plant bioactive compounds have shown digestive enzyme inhibition abilities with their capability to bind to enzyme protein (Paul and Majumdar, 2021). Besides, dietary fibers and their gelatinous polysaccharides have been proved to play a major role in the reduction of postprandial plasma glucose levels in DM.…”
Section: Research Paper Open Accessmentioning
confidence: 99%
See 2 more Smart Citations